Lipid profile and anthropometric parameters for health promotion in type 2 diabetic mellitus patients from Parnaíba-PI (Research, Society and Development, 2022)
Epidemiological evidence indicates that patients with type 2 Diabetes Mellitus (DM2) are increased risk of developing cardiovascular diseases, among the risk factors are obesity, overweight and dyslipidemia. To investigate the lipid profile and anthropometric indicators of abdominal obesity in a group of patients with DM2 from Parnaíba-PI. A cross-sectional, descriptive study was carried out with 51 individuals with DM2. Fasting glucose, glycated hemoglobin (HbA1c), triglycerides, HDL-c and LDL-c were measured. The measures of weight, height, waist circumference (WC) and hips were obtained and used to obtain the Body Mass Index (BMI), waist to height ratio (WHtR) and waist to hip ratio (WHR). Student's t and Mann-Whitney tests were used. Results: The observed population had 68.62% female and 31.37% male, with age of 59.12 ± 6.3 years. The diagnosis time was 8.3 ± 5.3 years. Hypercholesterolemia was prevalent at 725%, hypertriglyceridemia at 65%, and mixed hyperlipidemia at 6%. The reduction in HDL-c was observed in 61% of patients. Considering the normal LDL-c value ≤100 mg / dL, hypercholesterolemia alone had a prevalence of 90.19% and mixed hyperlipidemia in 29.41%. Mean blood glucose was 133.025 ± 52 mg/dL, and HbA1c levels ranged from 5.7-7.6%. Abdominal obesity obtained by the WC indicator was 75% and the WHtR was 91.66%. WHR was observed above the recommended values in 67.34% of patients. The high prevalence of abdominal obesity and lipid changes show the need to develop health practices that encourage healthy eating, physical activity and weight loss, since dyslipidemia in patients with DM2 has an important relevance for cardiovascular risk.